CONVENTION REPORT. (The Accounting Review, 1941)
The article presents information about the twenty-fifth annual convention of the American Accounting Association was held at the Blackstone Hotel in Chicago, Illinois, on December 27-28, 1940. The Chairman of the first session was Howard C. Greer, Vice President, Kingan and Co. in Indianapolis, Indiana. Papers discussed in the first session includes "Determining the Current Financial Position of a Municipality," by Arthur N. Long, University of Washington "The Accounting Provisions of the Investment Company Act of 1940," by Frank P. Smith, University of Rochester. The second session was headed by Victor H. Stempf, Toucher Niven and Co., New York City, and President, National Association of Cost Accountants. Papers that were discussed in the second session included "Stock Dividends," by Thomas York, The Ronald Company, New York City. President of the Association introduced the guests of the Association and read a telegram from the President of the New York State Society of Certified Public Accountants congratulating the Association on the twenty-fifth anniversary. Secretary-Treasurer of the Association presented a report of the membership and of the financial condition of the Association which is included in the auditor's report.